Mapping the Nexus between Organizational Culture, Workforce Skills and Construction Safety: Insights from CiteSpace Analysis - Li, Yikun; Hamrila, Abdul Latip; Fu, Ruichi (Human Resource Management Academic Research Society, 2025)
Organizational culture and workforce skills play a crucial role in enhancing construction safety performance and reducing accident rates. This paper aims to systematically analyze the internal connection between organizational culture, workforce skills, and their impact on construction safety performance. Using CiteSpace knowledge mapping software, academic literature related to construction safety from 1991 to 2023 was selected for bibliometric analysis to identify the spatial and temporal distribution and emerging research hotspots. By positioning construction safety within broader social science debates on organizational behavior and human capital, the study explores the evolutionary path of the role of organizational culture and workforce skills in construction safety. The findings reveal that research in construction safety has shifted from a focus on technical aspects to an increasing emphasis on factors such as organizational culture and workforce skills. "Safety culture", "workforce skills", and "behavior management" are identified as key future research areas. The interplay between organizational culture and workforce skills is shown to mirror wider social scientific concerns regarding how organizational environments shape worker behavior, and is recognized as a crucial factor in improving safety performance. The results of this study provide new theoretical support and practical guidance for future research on soft factors in construction safety management.